Low-frequency waterborne sound insulation by an acoustic metascreen with a metal chiral structure - Wang, Chao; Zhao, Honggang; Wang, Yang; Zhong, Jie; Yang, Haibin; Yu, Dianlong; Wen, Jihong (Frontiers in Materials, 2022)
Low sound speed or low-density materials can be used as soft acoustic boundaries in water, potentially as low-frequency underwater sound insulation. This study uses a chiral structure to construct an acoustic metascreen with deep subwavelength thickness. The results show that the transmission coefficient of the metascreen decreases noticeably in the low-frequency range when adjusting the chiral structure. The displacement pattern and the effective acoustic impedance are used to investigate the sound insulation mechanism. Low sound speed and effective acoustic impedance are found in the anisotropic chiral structure, and an extensive range of quasi-longitudinal wave phase velocities from 116.70 m/s to 3935.48 m/s can be obtained by adjusting the structural parameters without changing the filling rate. Finally, the effect of the oblique incidence angle on the sound insulation of the metascreen is investigated.